Advances in ecopolitics - Barry, John 1966- (Emerald, 2009)
This is a challenging time to be an academic with an interest in either the economy or the environment: we are being deluged with an over-supply of bad news. From the evidence of accelerating climate change to the increasingly desperate policies of fiscal stimulus and quantitative easing it is difficult enough to keep up with the jargon, never mind the policy. Academics tend to spend their careers looking backwards, analysing what is already safely established and categorized. The present crisis has deprived us of that luxury. Now more than ever our insights and our information are needed to save humanity from two interlinked crises that threaten our future. We need urgent solutions and we need co-operation: for this reason this issue includes contributions from academics and from campaigners. Many have questioned whether we have time to worry about the environment now that the financial crisis has become so pressing. What we seek to make clear in this special issue is that the two crises are in fact two aspects of the same crisis. It is a crisis of overconsumption, of debt-fuelled bingeing. It is a crisis of monetary-and-ecological debt; and of what happens when that debt starts to be called in.